Discontinuation of Postoperative Prophylactic Antibiotics for Endoscopic Endonasal Skull Base Surgery - Dastagirzada, Yosef; Benjamin, Carolina; Bevilacqua, Julia; Gurewitz, Jason; Sen, Chandra; Golfinos, John G.; Placantonakis, Dimitris; Jafar, Jafar J.; Lieberman, Seth; Lebowitz, Rich; Lewis, Ariane; Pacione, Donato (Journal of Neurological Surgery Part B: Skull Base, 2022)
Background Postoperative prophylactic antibiotic usage for endoscopic skull base surgery varies based on the institution as evidence-based guidelines are lacking. The purpose of this study is to determine whether discontinuing postoperative prophylactic antibiotics in endoscopic endonasal cases led to a difference in central nervous system (CNS) infections, multi-drug resistant organism (MDRO) infections, or other postoperative infections.Methods This quality improvement study compared outcomes between a retrospective cohort (from September 2013 to March 2019) and a prospective cohort (April 2019 to June 2019) after adopting a protocol to discontinue prophylactic postoperative antibiotics in patients who underwent endoscopic endonasal approaches (EEAs). Our primary end points of the study included the presence of postoperative CNS infection, Clostridium difficile (C. diff), and MDRO infections.Results A total of 388 patients were analyzed, 313 in the pre-protocol group and 75 in the post-protocol group. There were similar rates of intraoperative cerebrospinal fluid leak (56.9 vs. 61.3%, p = 0.946). There was a statistically significant decrease in the proportion of patients receiving IV antibiotics during their postoperative course (p = 0.001) and those discharged on antibiotics (p = 0.001). There was no significant increase in the rate of CNS infections in the post-protocol group despite the discontinuation of postoperative antibiotics (3.5 vs. 2.7%, p = 0.714). There was no statistically significant difference in postoperative C. diff (0 vs. 0%, p = 0.488) or development of MDRO infections (0.3 vs 0%, p = 0.624).Conclusion Discontinuation of postoperative antibiotics after EEA at our institution did not change the frequency of CNS infections. It appears that discontinuation of antibiotics after EEA is safe.
Keywords: endoscopic endonasal surgery; endoscopic endonasal approach; transsphenoidal; antibiotics; prophylaxis; pituitary